A cognitive behavioural preventative program for healthy eating and lifestyle for first year female students living in university residences - Palk, Gaby(Gabrielle Claire); Peck, Georgia Veronica (Stellenbosch : Stellenbosch University, 2012)
Thesis (M.A.) -- University of Stellenbosch, 1995.